Trans Health International Perspectives on Care for Trans Communities - Appenroth, Max Nicolai; Castro Varela, María do Mar (Gender Studies, 2022)
Around the world trans and gender diverse people are marginalized and discriminated against in medical, psychological, and nursing care. This anthology is the first to address the current situation of this population in various global healthcare settings. The perspectives from 11 different countries give insight into the difficult experiences of the trans and gender diverse community when seeking healthcare, and how self-organized community structures can help to overcome barriers to often inaccessible public healthcare systems. The majority of contributions are written from a lived trans and gender diverse perspective.